Job Stress can be a Great Hurdle in Goal-Focused Leader Behavior with the Mediating Role of the Bottom-Line Mentality of Leaders (Journal of Social Sciences Review, 2023)
The aim of this research study is to expand the literature regarding the interaction between job stress and workplace performance by establishing and justifying the relationship between job stress and goal-focused leader behavior (i.e., an important aspect of supervisory performance). Leaders who are goal-focused enable employees to achieve organizational goals by strategically using policies and practices to communicate and convey organizational goals and support their efforts to achieve them. To explain what makes a relationship work exists between job stress and supervisor bottom-line mentality (BLM), we also incorporate bottom-line mentality hypothesising. Exclusively, we propose BLM of the supervisor mediates the relationship between job stress and GFLB (goal-focused leader behavior). Employees (supervisors) of the banking sector in Punjab, Pakistan, collected data to examine the relationship between these variables. We used SPSS version 23 and Smart-PLS (v 4.0.9.0) to analyse the data and find the variables' impact using SEM analysis. The proposed theoretical model is tested through Smart-PLS (v 4.0.9.0). The study analysed 413 valid research questionnaires with a response rate of 83% through PLS-SEM to assess the relationship between the proposed theoretical model.
Keywords: Job stress (JS); Supervisor’s BLM (Bottom-line Mentality); Supervisor Goal Focused Leader Behavior (GFLB); PLS- SEM (Partial Least Squares Structural Equation Modelling)